EFFECT OF LATES CALCARIFER SEED STOCKING ON THE SURVIVAL AND PRODUCTION OF INDIAN MAJOR CARPS REARED IN A FRESHWATER COASTAL POND IN KONKAN REGION - SINGH, R. K.; SHINGARE, P. E.; CHAVAN, J. B.; SIDDIQUI, S. Q.; BELSARE, S. G. (Journal of Indian Fisheries Association, 2015)
The experiment indicated feasibility of culturing Indian major carps seedwith Lates calcarifer, if the size of Indian Major Carps is larger. In thepresent investigation the average growths of Catla catla, Labeo rohita andCirrhinus mrigala are recorded as 1193, 1120 and 821 g, respectively, duringthe year 1997-98, 1998-99 and 1999-2000 in 7.5 months. Complete haresting ofL. calcarifer is essential before stocking of new seed. The average growth ofL. calcarifer was recorded as about 670 g during the above period. About5000 numbers of Indian Major Carps fry per hectare can be stocked under thepresent culture system. Â·Keywords : Lates, survival, stocking